Kontribusi Kepemimpinan Kiai Dalam Pengembangan Kewirausahaan Pondok Pesantren - Supriyanto Supriyanto; Yulhendri Yulhendri; Delvia Safitri; Agung Sudjatmoko; Afi Rachmat Slamet (Jurnal Inovasi Pendidikan Ekonomi (JIPE), 2022)
Leadership in Islamic boarding schools is the leadership of caregivers or called cleric or master teachers. Leadership in developing entrepreneurship is also in the clergy. This study aims to interpret the role of cleric leadership in the development of entrepreneurship in Islamic boarding schools. This research uses a case study at the Sidogiri Islamic boarding school, Pasuruan. The unit of analysis of the research is ulama, teacher or cleric, business unit management, santri, community members of Islamic boarding school cooperatives. Data collection methods used in-depth interviews, participatory observation and content analysis of documentation. This research design uses a qualitative design with a case study model. Data analysis and data validity testing used triangulation techniques, namely source triangulation, method triangulation and time triangulation. The findings of this study indicate that Kiai's leadership plays an important role in the development of pesantren entrepreneurship. Kiai's important roles are (1) initiating, (2) facilitating, (3) mobilizing teachers, santri, and wali santi, and (4) mobilizing alumni to become investors in the pesantren business unit. Kiai also play a role in collaborating with other parties and the surrounding community.